Are Blood Cultures Useful in Patients with Skin and Soft Tissue Infections? - İlkay BOZKURT (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2018)
Introduction: Blood cultures are almost routinely performed in patients hospitalized with skin and soft tissue infections (SSTIs). The aim of this study was to evaluate the diagnostic importance of blood cultures in patients hospitalized with SSTIs. Materials and Methods: A total of 205 patients with cellulitis who were admitted to the adult Infectious Diseases and Dermatology Clinics at Ondokuz Mayıs University Hospital between January 2010 and June 2016, were included in the study. Data (including demographics, clinical characteristics, outcomes, number of radiologic and laboratory studies) were collected from electronic medical records. Results: Blood cultures and wound cultures were performed in 205 (100%) and 61 (29.8%) patients, respectively. Seven out of 205 (1.5%) blood cultures and 29 out of 61 (47.5%) wound cultures were positive (p<0.001). The positive blood cultures yielded beta-hemolytic streptococci (n=4), methicillin-sensitive Staphylococcus aureus (n=2) and Serratia marcescens (n=1). Methicillin-sensitive Staphylococcus aureus was isolated in 18 out of 61 (25.9%) wound cultures. 94 (46.3%) patients had a history of antibiotic use prior to hospitalization. Conclusion: Blood culture has a limited diagnostic value in the management of SSTIs. Clinicians should avoid performing unnecessary blood cultures in patients with cellulitis because of a lack of benefit and no contribution to patient management.